East African Indians: How Many Are They? - (:unkn) unknown (My University, 2010)
This chapter belongs to a multidisciplinary research carried out by the French Institute of Research in Africa, an organism relevant to the French Minister of Foreign Affairs. The research was directed by Michel Adam, anthropologist. Its objective were to allow a better knowledge of the Indian diaspora living in East Africa, in particular in its present characteristics analysed with qualitative (research fields close to the communities) and quantitative approaches. This document presents the demographic aspect of the research from the data available for Kenya, Uganda and Tanzania.
Keywords: African Research